Palaeoenvironmental changes based on foraminifera during the late Holocene at the Beagle Channel, Argentina - Bernasconi, Emiliana (2022)
A foraminiferal faunal study was carried out in a Holocene marine section from Arroyo Baliza, located on the northwest coast of the Beagle Channel, to contribute to the knowledge of the palaeoenvironmental conditions during the marine Holocene event. Foraminiferal assemblage was represented by 32 species distributed among 21 genera. The assemblage was dominated by Elphidium macellum (Fichtel & Moll) Elphidium alvarezianum (d’Orbigny), Cribroelphidium excavatum (Terquem) and Buccella peruviana (d’Orbigny), accompanied by Cibicides fletcheri Galloway & Wissler and Cibicidoides dispars (d’Orbigny) in low proportion. The predominance of Peridiniales dinocysts in the marine palynomorphs assemblage, suggested inner neritic conditions with cooler and more nutrient-rich waters. The distribution of the foraminiferal species was variable throughout the section indicating palaeoenvironmental changes in Arroyo Baliza between 3499–2595 cal yr BP. A gradual passage from high energy, cold and well-oxygenated marine waters towards a shallower environment with low energy and low to moderate salinity of the waters were linked to the regressive phase. This study complements and supports the previous palynological data from this section, which reflects an increase in number and diversity of dinocyst species indicating marine environmental conditions during the late Holocene as it exists today in the Beagle Channel.